2014
DOI: 10.1007/s10461-014-0850-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Directly Observed Antiretroviral Therapy Compared to Self-Administered Antiretroviral Therapy on Adherence and Virological Outcomes among HIV-Infected Prisoners: A Randomized Controlled Pilot Study

Abstract: The effect of directly observed therapy (DOT) versus self-administered therapy (SAT) on antiretroviral (ART) adherence and virological outcomes in prison has never been assessed in a randomized, controlled trial. Prisoners were randomized to receive ART by DOT or SAT. The primary outcome was medication adherence [percent of ART doses measured by the medication event monitoring system (MEMS) and pill counts] at the end of 24 weeks. The changes in the plasma viral loads from baseline and proportion of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In a South African prison, losses to follow up among 148 prisoners were high (22%) both during incarceration and after release but in the 70 patients who remained in care, 92% had an undetectable VL [16]. Our virological results and those of the South African study compare favourably with reports from prisons in affluent settings where rates of undetectable VL were between 50 and 74% [8][9][10][11] as well as with recent routinely collected VL data from the whole population on ART in Malawi, showing that 11% of VL results were >1,000 copies/ml [17].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In a South African prison, losses to follow up among 148 prisoners were high (22%) both during incarceration and after release but in the 70 patients who remained in care, 92% had an undetectable VL [16]. Our virological results and those of the South African study compare favourably with reports from prisons in affluent settings where rates of undetectable VL were between 50 and 74% [8][9][10][11] as well as with recent routinely collected VL data from the whole population on ART in Malawi, showing that 11% of VL results were >1,000 copies/ml [17].…”
Section: Resultssupporting
confidence: 63%
“…Few reports of ART outcomes in prisoners are available that include viral suppression rates. A small study of the impact of directly observed ART, conducted between 2003 and 2005, reported that 50% of American prisoners had undetectable VL 48 weeks after the intervention was introduced [8]. In Connecticut USA, 70% of 882 prisoners on ART between 2005 and 2012 had undetectable VL before release from prison [9] and achieving full viral suppression was associated with female gender and a lower psychiatric illness score.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, however, have shown that specific aspects of self-management are feasible and effective in prison. A randomized controlled trial demonstrated that adherence to self-administered HIV medications in prison is comparable to that administered in medication line (White et al 2015 ). Self-administered medications also promote patient confidentiality, are more tolerable to patients, and may potentially prepare patients for disease management upon release (Roberson et al 2009 ; Hassan et al 2012 ; Rieder et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Closed CJ settings include prisons, which houses inmates generally sentenced to >1 year and are under state or federal jurisdiction; jails or pre-trial detentions, which house inmates who are pre-adjudication or generally under local or state jurisdiction (33). HIV interventions involved psychoeducational risk reduction, intensive case management for discharge planning, HIV testing (34), adherence support (as directly administered antiretroviral therapy (35, 36),) and medication-assisted treatment for substance use disorders (including extended-release naltrexone (37), methadone (37), and buprenorphine (38). ) The majority of interventions were related to HIV prevention and testing for selected “high risk” women offenders, although risk (as either an inclusion criteria or a measured outcome) was variously defined.…”
Section: Resultsmentioning
confidence: 99%